Developing a Conceptual Framework for a Gender-Responsive Academic Service Information System in Islamic Higher Education: A Systematic Literature Review - Yosi Intan Yosi; Roqib; Feri Nuryadi; Imron Hamzah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2026)
This study aims to analyze the development of research on gender-responsive academic service information systems in higher education, identify the factors influencing their development, and develop a conceptual framework for a gender-responsive academic service information system in Islamic higher education. The study employed a Systematic Literature Review (SLR) using the PRISMA framework, encompassing the stages of identification, screening, eligibility assessment, and synthesis of the selected studies. The literature search was conducted using the Scopus database with the keywords “Gender Academic Services,” “Islamic Higher Education,” and “Academic Information Systems.” The initial search identified 211 articles, of which 18 met the eligibility criteria and were included in the final analysis. The findings indicate that the development of academic service information systems in higher education has evolved toward strengthening strategic information systems, digital literacy, user experience, governance, sustainability, and human-centered academic services. The study also found that the development of gender-responsive academic service information systems is influenced by technology quality, self-efficacy, resilience, leadership, organizational governance, and an inclusive educational culture. Furthermore, this study develops a conceptual framework that integrates technological aspects, user experience, institutional governance, service sustainability, and gender responsiveness within academic services in Islamic higher education. This study contributes to the advancement of Islamic Education Management scholarship by strengthening the paradigm of technology-based academic services and gender responsiveness.